2022
DOI: 10.3389/fonc.2022.775081
|View full text |Cite
|
Sign up to set email alerts
|

Dalpiciclib Combined With Pyrotinib and Letrozole in Women With HER2-Positive, Hormone Receptor-Positive Metastatic Breast Cancer (LORDSHIPS): A Phase Ib Study

Abstract: PurposeThe LORDSHIPS study aimed to explore the safety and efficacy of a novel fully oral triplet combination of dalpiciclib (a potent cyclin-dependent kinase 4/6 inhibitor), pyrotinib (a HER2 tyrosine kinase inhibitor) and endocrine therapy letrozole in patients with HER2-positive, hormone receptor (HR)-positive metastatic breast cancer (MBC) in the front-line setting.Patients and MethodsPostmenopausal women with HER2-positive, HR-positive MBC were recruited in the dose-finding phase Ib trial. A standard 3 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…14 Department of Anesthesiology, the First Affiliated Hospital of China Medical University, Shenyang, China. 15 Department of Biochemistry and Molecular Biology, Mayo Clinic College of Medicine, Rochester, MN 55905, USA. 16 Instituto Brasileiro de Controle do Câncer Oncologia (IBCC Oncologia), São Paulo, Brazil.…”
Section: Reporting Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…14 Department of Anesthesiology, the First Affiliated Hospital of China Medical University, Shenyang, China. 15 Department of Biochemistry and Molecular Biology, Mayo Clinic College of Medicine, Rochester, MN 55905, USA. 16 Instituto Brasileiro de Controle do Câncer Oncologia (IBCC Oncologia), São Paulo, Brazil.…”
Section: Reporting Summarymentioning
confidence: 99%
“…Preclinical studies have suggested that dalpiciclib can overcome the resistance to HER2-targeted blockade and endocrine therapy in ERpositive, HER2-positive breast cancer cells 14 . The phase 1b LORDSHIPS study has suggested a potentially synergistic anti-tumor effect with pyrotinib, letrozole, and dalpiciclib in front-line patients with HRpositive, HER2-positive metastatic breast cancer 15 .…”
mentioning
confidence: 99%
“…The toxicity of this treatment was tolerable. [11] In this case, we chose trastuzumab, leuprolide, letrozole, and piperacillin as first-line treatment regimens and achieved good therapeutic effects. The reasons for successful treatment in this case as follows: Expression of HR (ER 80% +, PR 60% +) and the biological characteristics of the patient's tumor were better than those with low HR expression, closer to HER2-negative and HR-positive breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeted combination endocrine therapy has the potential to replace traditional chemotherapy combined with anti HER2 targeted therapy in the population of TPBC advanced patients who have failed anti HER2 treatment. Zhang et al [31] conducted a Phase Ib clinical study(LORDSHIPS) on the first/second line treatment of advanced TPBC patients with a combination regimen of dalpiciclib, pyrotinib, and letrozole. The study included 15 patients with advanced TPBC, with a median follow-up time of 11.4 months.…”
Section: Discussionmentioning
confidence: 99%